THE RELATIONSHIP BETWEEN CLINICAL FACTORS AND OUTCOMES OF GASTROSCHISIS PATIENTS AT DR. ZAINOEL ABIDIN REGIONAL HOSPITAL, BANDA ACEH - Darul Ilham; Subhan, Nanda; Azmi Fanany, Muhammad (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
Background: Gastroschisis is an abdominal wall defect without a covering membrane, leaving intra-abdominal organs, particularly the intestines, exposed. Globally, the incidence varies, ranging from 0.22 to 7.91 per 10,000 live births.Objective: To determine the clinical associations of gastroschisis patients and identify risk factors that could potentially influence clinical outcomes at Dr. Zainoel Abidin Regional General Hospital, Banda Aceh. Methods: This retrospective observational study using medical records of patients with gastroschisis born between January 1, 2015, and December 31, 2018. Univariate and bivariate data analysis using the chi-square test with a P value <0.05. Results: In this study, the majority of patients were male (52.6%) with a birth weight ranging from 1,500 to 2,500 grams (63.2%). The most frequently performed intervention was primary closure (84.2%), predominantly conducted on day 0 of life (36.8%). A mild Apgar score was observed in 68.4% of the patients. There were statistically significant associations between survival duration and birth weight (p=0.016), type of surgical intervention (p=0.007), Apgar score (p=0.022), and timing of the intervention (p=0.000). Conclusion: Gastroschisis patients at this hospital are generally low-birth-weight boys born to young mothers. Factors such as birth weight, type of procedure, Apgar score, and age at procedure are associated with survival.